2007
DOI: 10.1002/ccd.21064
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal rhabdomyoma causing right ventricular inflow obstruction with duct‐dependent pulmonary blood flow: Successful stenting of PDA

Abstract: We describe an infant with the antenatal diagnosis of a large intracardiac rhabdomyoma causing tricuspid inflow obstruction. Postnatal cyanosis and arterial hypoxemia prompted commencement of intravenous prostaglandin E1 with immediate improvement in saturations. Clinical and genetic testing confirmed diagnosis of tuberous sclerosis. To secure ductal patency, two tandem coronary stents were implanted via an antegrade approach. Several episodes of long RP atrio-ventricular re-entrant tachycardia were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…[6][7][8][9][10] Multifocal tumors are associated with tuberous sclerosis in 78% to 95% of rhabdomyoma cases. 8,11 Spontaneous regression occurs during the first 2 to 4 years in 33% of these cases. 1 Tuberous sclerosis is an autosomal dominant neurocutaneous disease characterized by the presence of mass lesions in various organs including the brain, skin, kidney, liver, lung, and heart.…”
mentioning
confidence: 98%
“…[6][7][8][9][10] Multifocal tumors are associated with tuberous sclerosis in 78% to 95% of rhabdomyoma cases. 8,11 Spontaneous regression occurs during the first 2 to 4 years in 33% of these cases. 1 Tuberous sclerosis is an autosomal dominant neurocutaneous disease characterized by the presence of mass lesions in various organs including the brain, skin, kidney, liver, lung, and heart.…”
mentioning
confidence: 98%
“…Significant ventricular inflow or outflow obstruction associated with hemodynamic instability, however, may require early surgical resection of the tumor. 3,4 In this case, it was deemed that systemic perfusion was maintained by right ventricular ejection and nonrestrictive interatrial communication, even though the LV mass itself may have caused LV inflow and outflow obstruction. Because huge masses in the LV precluded us from performing early primary repair of TOF, we elected to perform a systemic-pulmonary shunt to defer definitive surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Among a series of 33 patients, 3 23% (n = 7) required surgical intervention for left ventricular outflow tract obstruction without any complications. Ilina et al 7 reported successful patent ductus arteriosus (PDA) stenting in a baby with a large intracardiac rhabdomyoma causing tricuspid inflow obstruction leading to cyanosis and hypoxemia. PDA stent was performed on day 11 of life and allowed discontinuation of prostaglandin and discharged home.…”
Section: Currently Established Treatmentsmentioning
confidence: 99%